Kekuatan Tanah Campuran (Tanah Laterit Dengan Kandungan Pasir Tertentu) Diuji Dengan Menggunakan Kaedah Macintosh, Piezocone, Ketumpatan Di Tapak Dan Ketumpatan Relatif - Che Hussin, Mohd Herzi (Universiti Sains Malaysia, 2006)
The main objective of this research is to set the best combination for the mixture of laterite dan sand for maximum California Bearing Ratio (CBR) reading. In the experiment involving sand-laterite mix ratios, each mix were tested for dry density, optimum moisture content, CBR and the piezocone resistance. Standard Proctor test is used for measuring optimum moisture content and maximum dry density. The moisture content will then be used in the CBR and the piezocone tests. It was found there are 2 peaks in the sand percentage versus California Bearing Ratio curve which suggests that any of the two sand-laterite mix ratios would improve strength of the mix. In the CBR test, the two peaks correspond to sand contents of 50% and 72%. For maximum dry density using standard Proctor, single peak correspond to an optimum moisture content of 60%. Mackintosh reading generally increase with increasing laterite content, at maximum dry density of mix ratios. The maximum tip resistance of the piezocone test corresponds to a sand content of 60%, however the sleeve friction was maximum at 10% sand content. Taking considerations of all mix ratios, maximum dry density reduces with optimum moisture content, which range from 10% to 12.5%.